(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2016)
Late blight caused by Phytophthora infestans (Mont.) de Bary, is one of the most significant constraints to potato production in Bale high lands and other regions of Ethiopia. Hence, this requires to develop high yielding and late blight resistant varieties. Therefore, this study was conducted to determine host resistance of potato against Phytophthora infestans in order to develop late blight resistant/tolerant genotypes. The experiment was laid out in randomized complete block design with three replications at Sinana Agricultural Research Center during 2014 main cropping season. The genotypes showed highly significant (P<0.01) differences for all the characters studied. Genotypes exhibited wide ranges of mean values for all characters. The highest total tuber yield (46.1 t ha-1) was obtained from the advanced clone, CIP-392640.524 followed by Belete (41 t ha-1). Late blight appeared early on farmer’s cultivar Kellacho (48 days after planting) and late on advanced clones CIP- 399062.102(74 days after planting). Percent severity index (PSI) and area under disease progress curve (AUDPC) ranged from 33.91 to 91.67% and 105 to 2370, respectively. Eleven newly introduced clones and the released variety "Belete" recorded PSI 33 to 39.7% and AUDPC 105 to 264.1. Hence, these genotypes can be categorized as moderately resistant. The study revealed the presence of considerable variability in tested genotypes for economically important traits and the higher chance of selecting genotypes with high yield and moderately resistant to late blight. However, it appears that further evaluation of genotypes across seasons and locations to identify genotypes that could be released as varieties seem to be quite pertinent. Int. J. Agril. Res. Innov. & Tech. 6 (1): 21-25, June, 2016